مناهج تفسير القرآن الكريم بين التقليد والتجديد The Methodology Interpretation of the Glorious Qur’an between Imitation and Innovation - عبد المجيد (Abu Saiid Muhammad Abdul Majid), أبو سعيد محمد (At-Tajdid - Intellectual Refereed Journal, 2010)
مستخلص البحث مر تفسير القرآن الكريم وتأويل آياته - شأنه شأن غيره من العلوم الإسلامية - بمراحل وأطوار شهد كلّ منها مناهجَ وطرائق قد تكون متوازية أو متداخلة، كما ظهرت في رحابه مدارس واتجاهات تتبنى هذا المنهج أو ذاك من مناهج التفسير والتأويل أو تُعمل أكثر من منهج في الوقت نفسه. وكل ذلك إنما كان سعياً للكشف عن معاني آيات الكتاب الحكيم وإدراك مراد الله تعالى فيها. ويسعى هذا المقال إلى تقديم عرض تاريخي عام لمناهج التفسير والتأويل، ناظراً إليها من زاويتي التقليد والتجديد بحسبان ذلك تعبيرًا عن تفاعل التفسير مع تطورات الحياة ومتطلباتها. الكلمات الأساسية: القرآن، التفسير، التأويل، مناهج التفسير، التقليد، التجديد. Abstract Like other Islamic disciplines, the interpretation of the Qur’an and explication of its verses went through different stages of developments. Each stage witnessed different approaches and methods that may operate separately and in parallel to each other or in connection with one another. There also appeared different exegetic schools that may use one or more than one exegetic method in interpreting the Qur’an. All this came about in pursuit of the meanings of Qur’anic verses and in search of God’s intent in them. This article attempts to provide a general historical account of the exegetic methods, with a view to bringing to the fore the perspectives of both imitation and innovation in those methods as a manifestation of the interaction Qur’anic exegesis with the changes and demands of life. Key terms: Qur’an, exegesis, interpretation, exegetic methods, imitation, innovation. Abstrak Seperti disiplin ilmu Islam yang lain, penafsiran Al-Qur’an dan penjelasan dari ayat-ayatnya melewati berbagai tahap perkembangan. Setiap tahap menyaksikan pendekatan yang berbeza dan kaedah yang boleh beroperasi secara berasingan dan peralel satu sama lain atau menyatukan pelbagai pendekatan untuk mencari maksud Tuhan pada setiap ayat al-Qur’an. Ada juga muncul kajian tafsir yang boleh menggunakan satu atau lebih satu kaedah tafsir dalam menafsirkan Al-Quran. Artikel ini cuba untuk memberikan laporan sejarah umum kaedah tafsir, dengan maksud untuk membawa perspektif baik imitasi dan inovasi dalam kaedah-kaedah sebagai manifestasi dari interaksi penafsiran Al-Quran dengan perubahan dan tuntutan kehidupan.. Kata kunci: Al-Quran, tafsir, tafsiran, kaedah penafsiran, imitasi, inovasi.